Language of Mathematics — A Corpus based Analysis of Textbooks - Meganathan, Ramanujam (THE PRIMARY TEACHER, 2017)
This paper tries to explore how Teaching Learning Materials (TLMs) for mathematics, particularly, textbooks developed by the National Council of Educational Research and Training (NCERT), recognise the importance of language in and for learning of mathematics. This has been done through an analysis of mathematics textbooks for Classes V, VI and VII. The paper tries to explore the role of language in teaching and learning of mathematics as realised in the textbooks. Besides, it tries to find out if mathematics textbook developers understand the role of language in explaining mathematical concepts.